Synthetic inquiry of four-letter words - Young, Amy Denise, author; Tornatzky, Cyane, advisor; Bukowski, Kristen, committee member; Harrow, Del, committee member; Taylor-Massey, Julie, committee member (Colorado State University. Libraries, 2021)
Four-letter words bear a few of the more intense emotional descriptors in the English language: love, hate, lust, and envy. My thesis series focuses on love but explores each of these four-letter words to display the complexity of human emotion. Each artwork in the series can be thematically categorized using love in relation to the dynamics of friendships, family, romance, or self. My thesis works reinterpret my experiences with themes of love and other four-letter words as an adolescent. The weavings depict and challenge rites of passage in American traditions and practices. Through weaving and reconstruction of items acquired in second-hand stores, I investigate human development and my own identity. The synthetic items found in thrift stores are manipulated to create factitious representations of my experiences and fantasies. In the safety of my studio and at the comfort of the loom, I inquire how these four-letter words shape and impact the recollection of my life up to this point. In this paper, my practice is detailed in two segments: Form and Themes. Form illustrates the physical labor of my studio practice which involves second-hand shopping, collage, weaving, and material-based processes. The theme segment relays the conceptual research that supports the artworks. Youth, love, and diversity are analyzed as linked themes through the lens of academia and cinema. Synthetic Inquiry of Four-Letter Words exhibits structures of interwoven thread, material, experiential information and investigation of identity.
Keywords: thrift stores; adolescence